Sleep Disordered Breathing in Adults with Cerebral Palsy: What Do We Know So Far?. Issue 6 (June 2021) - Hayward, Hannah; Louis, Mariam; Edwards, Linda; Jacob, Rafik
Abstract : Abstract: As advances in medicine continue to extend the lifespan of patients with cerebral palsy (CP), emphasis must be placed on evaluating patients for chronic health issues common in the general adult population. Sleep-disordered breathing (SDB) affects a large number of otherwise healthy adults and is even more common in individuals with disability. SDB includes the following subtypes: obstructive sleep apnea, central sleep apnea, and sleep-related hypoventilation/hypoxemia. SDB consequences include poor daytime functioning from sleepiness and an increased risk of cardiovascular morbidity and mortality. There is a paucity of data available in the literature about the association between SDB and CP in the adult population. More research is needed to understand the true prevalence and management strategies of SDB in patients with CP. This review focuses on three major subtypes of SDB: obstructive sleep apnea, central sleep apnea, and sleep-related hypoventilation/hypoxemia. Abstract : As advances in medicine continue to extend the lifespan of people with cerebral palsy (CP), emphasis must be placed on evaluating patients for chronic health issues that are common in the general adult population. Obstructive sleep apnea affects a large number of otherwise healthy adults and is even more common in individuals with disability. Its consequences include poor daytime functioning from sleepiness and an increased risk of cardiovascular morbidity and mortality. There is a paucity of data available in the literature regarding the association between obstructive sleep apnea and CP in the adult population. As such, more research is needed to understand the true prevalence of sleep disorders in patients with CP.